Prevalence of low energy availability among female athletes: A tier-based perspective from recreational to professional levels - Wagner, A.; Benícková, M.; Bulínova, V. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
This study assesses the prevalence of Low Energy Availability (LEA) among female athletes across four performance tiers, exploring its association with health and physiological metrics, including body weight, injury prevalence, gastrointestinal symptoms, and menstrual function. Surprisingly, the risk of LEA did not significantly vary across performance levels, challenging the expectation that elite athletes would exhibit a higher risk. This suggests that other factors, such as nutritional knowledge, substantially influence LEA risk among athletes of all tiers. The significant link between high performance and menstrual dysfunction further illustrates the complex effects of LEA on female athlete health. The study`s reliance on self-reported data indicates the need for further objective research to validate these findings.